2011
DOI: 10.1021/ma102708b
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt Ferrite Nanoparticles as Multifunctional Cross-Linkers in PAAm Ferrohydrogels

Abstract: Ferrohydrogels are synthesized by incorporation of magnetic CoFe2O4 nanoparticles into a polyacylamide hydrogel network during the polymerization process by utilizing different cross-linking units. Conventional cross-linked ferrohydrogels, using a molecular cross-linker, are compared to those obtained by our new approach where the magnetic particles, surface-functionalized with methacylic groups, serve as sole, multifunctional cross-linkers. Both experimental series are analyzed with regard to their swelling b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
157
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 134 publications
(159 citation statements)
references
References 29 publications
2
157
0
Order By: Relevance
“…9 Permanent linkage to the network also prevents nanoparticles from diffusing out of the gel, thereby limiting the loss of responsive materials and the potential toxic effects in biomedical applications. 62 These covalent NP-gels provide a system with better-defined coupling between nanoparticles and polymer matrix and thus open a way for better understanding of material structure-property relationship and subsequent modification for improved drug delivery properties.…”
Section: Stimuli-responsive Drug Deliverymentioning
confidence: 99%
“…9 Permanent linkage to the network also prevents nanoparticles from diffusing out of the gel, thereby limiting the loss of responsive materials and the potential toxic effects in biomedical applications. 62 These covalent NP-gels provide a system with better-defined coupling between nanoparticles and polymer matrix and thus open a way for better understanding of material structure-property relationship and subsequent modification for improved drug delivery properties.…”
Section: Stimuli-responsive Drug Deliverymentioning
confidence: 99%
“…Messing et al [9] reported on the transfer of CoFe 2 O 4 nanoparticles from nonpolar to aqueous media, while at the same time, the surface was functionalized so that the nanoparticles functioned as cross-linkers in a poly(acryl amide) gel. Establishing the function of the nanoparticles as cross-linkers was demonstrated by leakage experiments and by dissolution of the particles upon which the hydrogel fully disintegrated.…”
Section: Introductionmentioning
confidence: 99%
“…In reality, it can for example be tuned during synthesis by the way of embedding the magnetic particles in the polymer matrix. For instance, rotations of elongated magnetic particles [38] are hindered when compared to spheres, and magnetic particles that are actually part of the network due to chemical surface functionalization [6,7] experience permanent restoring torques under reorientation [8].…”
Section: Impact Of Orientational Memorymentioning
confidence: 99%